2022
DOI: 10.1002/esp.5475
|View full text |Cite
|
Sign up to set email alerts
|

Particle saltation trajectories in supercritical open channel flows: Roughness effect

Abstract: Bed load sediment transport governed by particle saltation in supercritical open channel flows causes bedrock incision in high-gradient mountain streams and hydroabrasion at hydraulic structures. Hence, a better understanding of turbulent flow characteristics and particle dynamics is of prime importance for the prediction of river and landscape evolution, and for a sustainable design of hydraulic structures. To this end, we experimentally investigated single-particle dynamics in supercritical open channel flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 77 publications
(266 reference statements)
3
8
0
1
Order By: Relevance
“…Five minutes of data has been used to get a mean flow velocity and a standard deviation. As the width-to-depth ratio in our present experimental set-up was about 4, there was uncertainty in the generation of secondary currents (Albayrak & Lemmin, 2011;Demiral et al, 2022).…”
Section: Flow Profilesmentioning
confidence: 82%
See 2 more Smart Citations
“…Five minutes of data has been used to get a mean flow velocity and a standard deviation. As the width-to-depth ratio in our present experimental set-up was about 4, there was uncertainty in the generation of secondary currents (Albayrak & Lemmin, 2011;Demiral et al, 2022).…”
Section: Flow Profilesmentioning
confidence: 82%
“…Auel et al (2017a) conducted experiments on smooth beds and indicated that saltating particle trajectories were rather flat and elongated compared with alluvial beds. Recently, Demiral et al (2022) have suggested that saltation trajectories are more vertical with increasing bed roughness. Thus the bed roughness would tend to change the length-to-height ratio of the trajectory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing ( 26) Agostini et al, 2022;Atwood & West, 2022;Davies et al, 2022;Davis et al, 2021;Fadul et al, 2022;Gervasi et al, 2021;Hendrickx et al, 2022;Hodge & Buechel, 2022;Hooke, 2022;Hovenga et al, 2021;Konlechner & Hilton, 2022;Lefebvre et al, 2022;Marchetti et al, 2022;McKenzie et al, 2022;Mol & Grenfell, 2022;Opalka et al, 2022;Rabanaque et al, 2022;Regalla et al, 2022;Reitman et al, 2022;Sampietro-Vattuone et al, 2021;Schoch-Baumann et al, 2022;Thompson et al, 2022;Vah et al, 2022;Valentine et al, 2022;Zhang et al, 2022 Physical experiments (8) Bako et al, 2022;Bywater-Reyes et al, 2022;Demiral et al, 2022;Friedrich et al, 2022;Negreiros et al, 2022;Rachelly et al, 2022;Roelofs et al, 2022;Vah et al, 2022 Numerical models ( 11) Agostini et al, 2022;Bywater-Reyes et al, 2022;Cullen et al, 2022;Glover et al, 2022;Hodge & Buechel, 2022;Kooijma...…”
Section: Papers Addressing Hillslopes and Mass Movements Includeunclassified
“…Many of the major research directions in contemporary geomorphology are reflected in this collection of papers. With respect to fluvial environments, including alluvial fans, individual papers examine use of images to detect sediment motion during physical experiments (Vah et al, 2022); comparison of grain‐size distributions from field measurements and remotely acquired images (Marchetti et al, 2022); physical experiments on bedload saltation under differing conditions (Demiral et al, 2022); numerical modelling of critical shear stress for grain entrainment based on imagery of bed‐rock channels (Hodge & Buechel, 2022); biogeomorphology (Bywater‐Reyes et al, 2022; Gurnell et al, 2022); channel morphology and classification (Lane et al, 2022), hydromorphology of ephemeral streams (Rabanaque et al, 2022) and interpretation of geomorphic unit assemblages (Fryirs & Brierley, 2022); flood effectiveness (Gervasi et al, 2021); channel evolution, terraces and sediment sources (Guyez et al, 2022) and the influence of sediment supply on gravel‐bed river widening (Rachelly et al, 2022); hydrological variation and meander morphodynamics (Hooke, 2022); the dynamics of wood in river corridors (Guiney & Lininger, 2022; Gurnell et al, 2022; Wohl, 2022) and numerical modelling of wood‐related processes (Friedrich et al, 2022); numerical model validation (Negreiros et al, 2022) and numerical modelling of groundwater‐driven network evolution (Cullen et al, 2022); base‐level controls and landscape evolution (Fadul et al, 2022); long‐term dryland channel response to urbanization (Chin, 2022); watershed restoration and management, including human alterations of process and form (Atkins et al, 2023; Davis et al, 2021; Goodman et al, in press; Gurnell et al, 2022; Hinshaw et al, 2022; Mossa & Chen, 2022; Sampietro‐Vattuone et al, 2021; Valentine et al, 2022); and alluvial fan dynamics (Opalka et al, 2022; Quock et al, 2022; Regalla et al, 2022; Schoch‐Baumann et al, 2022). Papers addressing process and form in coastal environments include examinations of dune morphodynamics and evolution (Hovenga et al,...…”
Section: Research Questions and Techniquesmentioning
confidence: 99%